The Urgence Of The Control Mechanism Of Authority The Prosecutor General In Waiting The Case For Public Interest (Seponeering) - Apriyanto NUSA; I Nyoman NURJAYA; Abdul MADJID; Bambang SUGIRI (Indonesia Strategic Sustainability, 2022)
The urgency of the control mechanism over the Attorney General's authority in overriding cases in the public interest (seponeering) is a manifestation of obtaining protection of human rights for every citizen who is harmed by the issuance of seponeering by the Attorney General. Apart from these reasons, the importance of controlling the authority of the Attorney General is also to create the principles of justice and legal certainty. Legal practices that often occur in the judicial process show stagnation in realizing these three things, both the protection of human rights (HAM), justice and legal certainty. Whereas the spirit of forming the Criminal Procedure Code which was promulgated based on Law Number 8 of 1981 laid the basic foundation for the protection of human rights (HAM) as the main goal, which includes upholding justice and legal certainty. There is stagnation in the effort to control the seponeering issued by the Attorney General, because there are juridical limitations in the pretrial object institution as stated in the Elucidation of Article 77 of Law Number 8 of 1981 concerning the Criminal Procedure Code which states that: with